Sodium alginate-guar gum and carbopol based methotrexate loaded mucoadhesive microparticles for colon delivery: An in vitro evaluation (Brazilian Journal of Pharmaceutical Sciences, 2022)
Methotrexate (MTX) is famous for its therapeutic potential against different cancers including colorectal cancer. Goal of the present investigation was to formulate MTX loaded mucoadhesive microparticles for colon targeting. The optimized formulation (MTX-MS2) was composed of mucoadhesive polymers (sodium alginate, guar gum and carbopol 940) in an appropriate ratio. MTXMS2 was developed by ionic-gelation method. The suitable particle size and zeta potential were found to be 21.10 ± 0.18 μm and 3.01 ± 0.16 mV for MTX-MS2 respectively. The % yield (98.60 ± 2.12), % entrapment efficiency (97.98 ± 1.22) and % drug loading (1.04 ± 0.03) were estimated for MTXMS2. The swelling index (0.99 ± 0.04 θ) and mucoadhesion (97.29 ± 4.61%) were significantly (***P ˂ 0.01) achieved with MTX-MS2 as compared to other formulations. The optimum drug release (96.07 ± 4.52%) was significantly achieved with MTX-MS2 at simulated gastric fluid (pH 7.4) for 36 h in a sustained manner. This profile may be attributed towards excellent mucoadhesivness of thepolymers used in the formulation. Therefore, the current investigation suggests that mucoadhesive carrier system could be promising approach for colon delivery. Thus, the proposed work would be helpful for the treatment of colorectal cancer.